2002
DOI: 10.1002/1099-0682(200203)2002:4<901::aid-ejic901>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

A Calix[4]arene-Based Bipyridine Podand as Versatile Ligand for Transition Metal Cations

Abstract: The calix[4]arene‐based podand 1 which incorporates two 2,2′‐bipyridine units and two benzyl units in alternate positions at the lower rim has been subjected to complexation studies with copper(I), copper(II), cobalt(II), nickel(II), and zinc(II). The reaction of 1 with Cu(MeCN)4PF6 afforded the expected mononuclear CuI complex. With cobalt(II), nickel(II), and zinc(II) chloride, 1 gave dinuclear tetrahedral complexes in which each bipyridine unit is associated to two chlorine atoms around the metal centre. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Regnouf-de-Vains and co-workers synthesised a calix [4]arene derivative containing two 2,2'-bipyridine and two benzyl groups in alternate positions at the lower rim [212] (Fig. 112).…”
Section: Extractionmentioning
confidence: 99%
“…Regnouf-de-Vains and co-workers synthesised a calix [4]arene derivative containing two 2,2'-bipyridine and two benzyl groups in alternate positions at the lower rim [212] (Fig. 112).…”
Section: Extractionmentioning
confidence: 99%
“…With the aim of producing cyclic polychelating structures that can exhibit colour changes due to ionic or molecular interactions, we decided to graft phenylazo groups as a signalling device [18] at the upper rim of thiacalix [4]arene and heterocyclic chelating agents such as 2,2'-bipyridyl and 2,2'-bithiazoly] groups at the lower rim. The incorporation of bilieterocycUc subunits has been chosen here because of their potential to complex various metal ions [19][20][21][22][23][24]. Thus, the presence of heteroatoms as bridging atoms in calixarene offers additional opportunities to modify the selectivity for binding ions [9].…”
Section: Introductionmentioning
confidence: 99%
“…18 It has been shown that calixarene derivatives integrating two 2,2 0 -bipyridine chelating units in alternate positions of the lower rim gave tetrahedral mononuclear complexes with Cu(I) salts and zinc triflate, and a dinuclear species with zinc chloride. 19 With the objective of developing extracting polymers incorporating such calixarene-bipyridyl units, we describe in the present report (i) the synthesis of a new bifunctional calix[4]arene species, aimed at complex ions with tetrahedral coordination geometry and incorporating for this purpose two 6-methylene-[6 0 -methyl-2,2 0 -bipyridine]yl arms in alternate position of the lower rim, and a p-aminoethyl-phenoxypropyl attachment group on one of the two residual phenol units; (ii) the grafting of this compound on Wang-benzaldehyde resin; and (iii) the simultaneous evaluation of grafting efficiency and some complexation properties towards copper(I) and zinc(II) species of the new materials, using UV/visible spectrophotometry and ionic chromatography.The bis-bipyridyl calix[4]arene 1, prepared according to the literature, 20 was reacted with (p-boc-aminoethyl)phenyl-(3-bromopropyl)ether 21 in dry DMF and NaH, to give the podand 2 with a yield of 80%. The Boc-protective group was removed by treatment 0040-4039/$ -see front matter Ó…”
mentioning
confidence: 99%
“…By analogy with similar ligands, 19 2 should give tetrahedral mononuclear complexes with Cu(I) salts and zinc triflate, and a dinuclear species with zinc chloride. As shown in Figure 1, the addition of Cu(MeCN) 4 PF 6 to a solution of 2 in CH 2 Cl 2 resulted in the bathochromic shift of the bipyridyl transitions from 290 nm to 302 nm, with an isosbestic point at 296 nm, and the appearance of the expected MLCT (Metal-to-Ligand Charge Transfer) band at ca.…”
mentioning
confidence: 99%
See 1 more Smart Citation